The Effect of Commissioners Board Size and Committee Board Size on Disclosure of Corporate Social Responsibility (CSR) - Hafidzi, Achmad Hasan (Agregat: Jurnal Ekonomi dan Bisnis, 2019)
This study aims to analyze the effect of board size and committees size to corporate social responsibility through financial performance. The sample used in this study is secondary data of companies listed LQ- 45 Index in 2013-2017 and determined using a purposive sampling method. The data about research variables are available in the financial report. The data analysis method is using path analysis. The results were showed that the size of commissioners board to corporate social responsibility was significant positive, size of committees to corporate social responsibility was significant positive relationship, size of commissioners board to financial performance was significant positive relationship, size of committees to financial performance was relationship positive significant, financial performance to corporate social responsibility shows a significant positive relationship.